Constructing Perceived Consumer Value Through Digital Financial Transformation and Green Marketing: The Case of KFC Indonesia – Centre Point Medan: Membangun Nilai Konsumen yang Dirasakan Melalui Transformasi Keuangan Digital dan Pemasaran Hijau: Studi Kasus KFC Indonesia – Centre Point Medan - Steven; Irvan Rolyesh Situmorang (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
Rapid growth in business has increased competition among companies, leading to the need for effective marketing approaches. This study seeks to examine the relationship between the use of financial technology, green marketing practices, and how customers view their purchasing experience at the KFC branch located in Centre Point, Medan. The study's population included all customers of KFC Centre Point during the research period. A sample of 120 participants was selected, determined through the Hair et al. formula with a 5% margin of error. The findings show that fintech adoption has a partial effect on perceived value at the KFC Centre Point Medan branch, and green marketing also has a partial effect on perceived value. Additionally, both fintech adoption and green marketing together have an impact on perceived value at the KFC Centre Point Medan branch.